Management of enteroatmospheric fistulae - Terzi, Cem (Int Wound J, 2014)
A small‐bowel enteroatmospheric fistula (EAF) is an especially challenging complication for patients with open abdomens (OAs) and their surgeons. Manipulation of the bowel during treatment (e.g. dressing changes) is one of the risk factors for developing these openings between the atmosphere and the gastrointestinal tract. Unlike enterocutaneous fistulae, EAFs have neither overlying soft tissue nor a real fistula tract, which reduces the likelihood of their spontaneous closure. Surgical closure is necessary but not always easy to do in the OA environment. Negative pressure wound therapy (NPWT) has been used successfully as an adjunct therapy to heal the wound around EAFs. This review discusses many aspects of managing EAFs in patients with OAs, and presents techniques that have been developed to isolate the fistula and divert effluent while applying NPWT to the surrounding wound bed.